Mapping valence band and interface electronic structure changes during the oxidation of Mo to MoO3 via MoO2 and MoO3 reduction to MoO2: A NAPPES study - Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Tuning the surface energetics, especially work function (phi) of the materials, is of a great deal of interest for a wide range of surface- and interface-based devices and applications. How the phi of a solid surface changes under the reaction conditions is of paramount interest to the chemists, particularly in the areas of surface dependent phenomena such as, catalysis and electrochemistry. In the present study, by using the valence band and core-level photoelectron spectroscopy, surface-electronic changes from Mo to MoO3 via MoO2 was studied under relevant near-ambient pressure (NAP) and high temperature conditions. A very significant change in phi from Mo to MoO3 was observed and it is well corroborated with the changes in gas-phase vibrational features of O-2 in both near-ambient pressure ultraviolet photoelectron spectra (NAPUPS) as well in NAP X-ray photoelectron spectroscopy. Reversible changes in the electronic structure is observed when MoO3 was reduced in H-2 to MoO2. On the basis of the extent of oxidation/reduction of MoOx NAPUPS has shown, one or two additional peaks in the band gap at 0.6 and 1.6 eV below the Fermi level. Mo5+ features are identified in the VB and in the Mo 3d core levels with distinct features. Mo5+ features are also stable and essential to bridge MoO2 and MoO3 layers, and their co-existence. In addition, characteristic changes in Mo 4d and O 2p features observed from Mo to MoO3 and well corelated to the band gap of MoO3. Oxidation and reduction propagate from the surface to bulk; indeed, this has significant implications in surface-dependent phenomena. The present study demonstrates (a) the uniqueness of NAPUPS in identifying the subtle to large changes in the electronic structure on solid surfaces under common oxidation and reduction (in general, under reaction) conditions, and (b) relevance of NAPUPS to all surface dependent phenomena, such as catalysis and electrochemistry.